Efektivitas Penerapan Aplikasi Akuntansi Berbasis Web dalam Penyusunan Laporan Keuangan UMKM sesuai SAK EMKM - Alrizwan, U. Ari; Noviriani, Eliza; Herjiden; Sari, Indah Permata; Khalisa (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
The weaknesses of MSMEs in preparing financial reports can be overcome by using accounting applications that are widely available, both desktop-based, Android, and web-based. The purpose of this study is to obtain evidence that the POS and MSME Accounting Application can be used effectively in preparing and presenting the financial reports of Toko Bangunan Usaha Kita in accordance with SAK EMKM. The research method used in this study is a descriptive method with a qualitative approach. The results of this study are that this application can be applied in preparing MSME financial reports with several stages, namely inputting data into the application (company profile, initial balance/capital, and data on all financial transactions in a predetermined period. After all the data is inputted into the application, it produces financial reports, namely the financial position report and the profit and loss report. The presentation of financial reports based on the output of the POS and MSME Accounting Application is in accordance with SAK EMKM where financial information is presented comparatively, but one financial report that should be there is missing, namely Notes to the Financial Statements. This deficiency can be overcome by creating the report using another application (Excel).